2001
DOI: 10.1111/j.1471-0528.2001.00036.x
|View full text |Cite
|
Sign up to set email alerts
|

Female genital mutilation: analysis of the first twelve months of a southeast London specialist clinic

Abstract: Objectives To analyse the sources and reasons for referral of women who have undergone genital mutilation to a recently established specialist clinic, and to determine the consequences of the genital mutilation procedure. Design Retrospective descriptive case series.Setting The maternity units of Guy's and St. Thomas's Hospital, London.Population One hundred and sixteen women attending the clinic over a one-year period. Main outcome measures (1) sources and reasons for referral to the specialist clinic; (2) ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0
4

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 24 publications
(35 reference statements)
0
33
0
4
Order By: Relevance
“…Female genital mutilation (FGM) encompasses all procedures involving partial or total removal of the external female genitalia or other injury to the female genital organs whether for cultural or other non-therapeutic reasons (WHO, 1997;Momoh et al, 2001). The World Health Organisation (1995) classifies female genital mutilation into four groups based on severity: Type I (excision of the prepuce and/or the clitoris), Type II (excision of the prepuce and clitoris with removal of the labia minora), Type III or infibulation (excision of the external genitalia with narrowing or stitching of the vaginal orifice) and Type IV (unclassified genital mutilation, including piercing, pricking, cauterising or cutting of the vulva).…”
Section: Introductionmentioning
confidence: 99%
“…Female genital mutilation (FGM) encompasses all procedures involving partial or total removal of the external female genitalia or other injury to the female genital organs whether for cultural or other non-therapeutic reasons (WHO, 1997;Momoh et al, 2001). The World Health Organisation (1995) classifies female genital mutilation into four groups based on severity: Type I (excision of the prepuce and/or the clitoris), Type II (excision of the prepuce and clitoris with removal of the labia minora), Type III or infibulation (excision of the external genitalia with narrowing or stitching of the vaginal orifice) and Type IV (unclassified genital mutilation, including piercing, pricking, cauterising or cutting of the vulva).…”
Section: Introductionmentioning
confidence: 99%
“…[4,6]. These studies have demonstrated the detrimental obstetric consequences of female genital mutilation.…”
Section: Discussionmentioning
confidence: 96%
“…Zoals uit eerder onderzoek is gebleken, worden met name huisartsen geconfronteerd met complicaties als gevolg van VGV. 15 Met medische klachten gaat men toch als eerste naar de huisarts en niet naar een specialist. De meerderheid van de professionals gaf aan een gemiddelde kennis over VGV te hebben.…”
Section: Beschouwingunclassified